Laparoscopic supramassive splenectomy weighing 1710 gm in a 17-year-old boy with a history of open heart surgery, transposition of great arteries and pulmonary artery stenosis with ventricular septal defect: a case report - Badipati, Raju; Kasinikota, Lakshmi D.; Gunturu, Kushal; B. , Haritha (International Surgery Journal, 2023)
When a spleen weighs more than 1,600 grams or has a craniocaudal length larger than 21 cm, it is categorized as a supramassive spleen. Laparoscopic splenectomy for normal to moderately enlarged spleens has become the gold standard in elective splenectomy surgery. Its utility in large splenomegaly has not yet completely established, but has great advantage over open surgery. Here, we present a case of 17-year-old young male with a history of congenital heart disease who underwent a Rastelli open heart surgery in 2010 and pulmonary balloon valvulotomy in 2022 came with supramassive splenomegaly, hypersplenism and pancytopenia that was treated with laparoscopic splenectomy. Vaccinations were done two weeks prior to the surgery. Preoperative embolization of the splenic artery was performed 24 hours before splenectomy to reduce complications. The excised spleen measured about 24×15 cm.